New Antimicrobials for Gram-Positive Sustained Infections: A Comprehensive Guide for Clinicians - Davide Carcione; Jari Intra; Lilia Andriani; Floriana Campanile; Floriana Gona; Silvia Carletti; Nicasio Mancini; Gioconda Brigante; Dario Cattaneo; Sara Baldelli; Mattia Chisari; Alessandra Piccirilli; et al. (MDPI AG, 2023)
Antibiotic resistance is a public health problem with increasingly alarming data being reported. Gram-positive bacteria are among the protagonists of severe nosocomial and community infections. The objective of this review is to conduct an extensive examination of emerging treatments for Gram-positive infections including ceftobiprole, ceftaroline, dalbavancin, oritavancin, omadacycline, tedizolid, and delafloxacin. From a methodological standpoint, a comprehensive analysis on clinical trials, molecular structure, mechanism of action, microbiological targeting, clinical use, pharmacokinetic/pharmacodynamic features, and potential for therapeutic drug monitoring will be addressed. Each antibiotic paragraph is divided into specialized microbiological, clinical, and pharmacological sections, including detailed and appropriate tables. A better understanding of the latest promising advances in the field of therapeutic options could lead to the development of a better approach in managing antimicrobial therapy for multidrug-resistant Gram-positive pathogens, which increasingly needs to be better stratified and targeted.